Charlie’s Fear of Abandonment in Stephen Chbosky’s The Perks of Being a Wallflower - ANDINI SWARI DEVINA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
AbstractThis study discuss about fear of abandonment on the main character named Charlie. The theory uses to analyse the studyis paranoid-schizoid position by Melanie Klein about children psychoanalysis. It focuses on the textual information on thenovel which made this study a descriptive qualitative study. The main data is taken from Stephen Chbosky’s The Perks ofBeing a Wallflower and journal articles as the supporting data. Charlie is the main focus of this study. This study’s purposesis to analyze the symptoms of fear of abandonment Charlie has and the factors that caused him to have this fear as hisdisplacement. The mechanism of this study is by analyzing the early mental state of Charlie with the paranoid-schizoidposition theory by Melanie Klein. The analysis point out that Charlie’s symptoms of having a fear of abandonment iscaused by trauma of being left by people he loves when he was a child and by the lack of love and affection he receivefrom his family. The analysis and discussion prove that Melanie Klein’s theory about the hunger of love and affection theadult may have when they grow up came from the absent of a mom figure which may result several displacement inadulthood including the fear of abandonment.Keywords: content, formatting, article